CD4+CD25highforkhead box protein 3+ regulatory T lymphocytes suppress interferon-γ and CD107 expression in CD4+ and CD8+ T cells from tuberculous pleural effusions - Geffner, Laura Judith (2014)
Tuberculous pleural effusion is characterized by a T helper type 1 (Th1) profile, but an excessive Th1 response may also cause tissue damage that might be controlled by regulatory mechanisms. In the current study we investigated the role of regulatory T cells (Treg) in the modulation of Th1 responses in patients with tuberculous (TB) pleurisy. Using flow cytometry we evaluated the proportion of Treg (CD4+CD25highforkhead box protein 3+), interferon (IFN)-γ and interleukin (IL)-10 expression and CD107 degranulation in peripheral blood (PB) and pleural fluid (PF) from patients with TB pleurisy. We demonstrated that the proportion of CD4+CD25+, CD4+CD25highFoxP3+ and CD8+CD25+ cells were increased in PF compared to PB samples. Mycobacterium tuberculosis stimulation increased the proportion of CD4+CD25low/negIL-10+ in PB and CD4+CD25low/negIFN-γ+ in PF; meanwhile, CD25high mainly expressed IL-10 in both compartments. A high proportion of CD4+CD107+ and CD8+CD107+ cells was observed in PF. Treg depletion enhanced the in-vitro M. tuberculosis-induced IFN-γ and CD4+ and CD8+ degranulation responses and decreased CD4+IL-10+ cells in PF. Our results demonstrated that in TB pleurisy Treg cells effectively inhibit not only IFN-γ expression but also the ability of CD4+ and CD8+ cells to degranulate in response to M. tuberculosis.